Experiment and analysis of strength behaviour of soil reinforced with horizontal–vertical inclusions. Issue 4 (August 2011) - Hou, J.; Zhang, M.X.; Javadi, A.A.; Peng, M.Y.
Abstract : ABSTRACT: By conducting a series of plane strain experiments on samples of a soil reinforced with new horizontal–vertical (H–V) reinforcing elements. The influences of minor principal stress, configurations of horizontal and H–V inclusions, and the height of vertical element on the behaviour of the soil are presented and discussed. The experimental results showed that the strength of the soil reinforced with H–V inclusions is higher than that of the sandy soil with horizontal inclusions. The strength of the soil reinforced with H–V inclusions rises with increasing height of the vertical elements, reinforcing ratio of the inclusions and the minor principal stress. Based on limit equilibrium theory, a strength model was developed for the soil reinforced with H–V inclusions under plane strain conditions. The predictions from the strength model are in good agreement with the experimental results.